Double diffusive convection in non-newtonian fluid flow with quadratic radiation and variable viscosity: Heat generation effects in lower stagnation point of solid sphere - Khadija Rafique; Zafar Mahmood; Ioan-Lucian Popa; Talha Anwar; Abhinav Kumar (Results in Engineering)
The examination of non-Newtonian nanofluid flows over curved geometries is essential for industrial and medicinal applications, including targeted drug delivery, thermal management in biomedical devices, and sophisticated cooling systems. Driven by the necessity of improved heat and mass transfer under challenging physical conditions, this work offers a thorough investigation of double-diffusive Casson nanofluid flow over a solid sphere at lower stagnation point flow in the presence of quadratic thermal radiation, heat generation, magnetic field effects, and variable fluid viscosity. Subject to mass suction at the surface of the sphere, the flow is characterized as consistent, laminar, and two-dimensional with mixed convection. The governing equations for momentum, energy, and concentration in the boundary layer are obtained and reformulated for numerical analysis using the Galerkin finite element technique. Important dimensionless factors used in parametric studies include Casson, buoyancy, buoyancy ratio, magnetic field intensity, Eckert, Lewis, thermal radiation, heat production, mass suction, and variable viscosity. Results show that raising the Casson parameter upsurges velocity while lowering temperature and concentration, hence improving Nusselt and Sherwood values. While magnetic field effects contribute to velocity augmentation under certain situations, suction increases wall shear and improves both thermal and solutal transport. Viscous dissipation and internal heat creation increase fluid temperature, hindering heat transport. As mass suction escalates from 0.5 to 2.0, skin friction has a 48.80 % increase, the Nusselt number rises by 450.22 %, and the Sherwood number grows by 47.12 %.